MANAJEMEN MASJID: PERSPEKTIF PEMBERDAYAAN MASYARAKAT - Gusriani, Raden Yani (UIN Antasari Banjarmasin, 2013)
In terms of quantity, there are a large number of mosques in Indonesia. They can be a potentially tremendous if managed properly, especially in the context of community empowerment. This article examines the application of management functions ie Planning, Organizing, Actuating and Controlling in managing the mosques. From the perspective of an integrated community development, the mosque can serve as an institution of social, economic, political, and public education development